Trans-Tenon's retrobulbar triamcinolone acetonide injection for macular oedema related to branch retinal vein occlusion. Issue 1 (26th October 2007) - Kawaji, T; Takano, A; Inomata, Y; Sagara, N; Iwao, K; Inatani, M; Fukushima, M; Tanihara, H
Abstract : Background: The aim of the study was to evaluate the safety and effectiveness of trans-Tenon's retrobulbar triamcinolone acetonide (TA) injection for macular oedema associated with branch retinal vein occlusion (BRVO). Methods: We reviewed the medical records of 50 consecutive patients with macular oedema associated with BRVO who were treated with trans-Tenon's retrobulbar TA injection (20 mg) as initial treatment for a follow-up period of at least 12 months. Foveal thickness determined by optical coherence tomography, visual acuity, intraocular pressure (IOP) and cataract progression were measured. Results: The mean duration between oedema onset and TA injection was 4.9 months. Foveal thickness decreased significantly at 3 months after injection (p<0.0001). Furthermore, the percentage reduction in foveal thickness in eyes with posterior vitreous detachment (PVD; n = 23) was significantly greater than that without PVD (n = 27, p = 0.003). Improved visual acuity by at least 0.20 log minimum angle of resolution (logMAR) was seen in 22 eyes (44%; 11 eyes with PVD and 11 eyes without PVD). After completion of the 3-month follow-up, 29 eyes (58%) needed additional treatment including TA injections or pars plana vitrectomy (PPV). PPV seemed to be effective for macular oedema resistant to TA. IOP elevation and cataract progression occurred in less than 10% of all patients. Conclusions: Trans-Tenon's retrobulbar TA injection appeared safe and relatively effective for macular oedema associated with BRVO. In eyes resistant to TA injection, PPV may be effective as an adjunctive treatment.